The essence of analgesia and analgesics - Sinatra, Raymond S.; Jahr, Jonathan S.; Watkins-Pitchford, J. Michael (Cambridge books online., 2011)
"The Essence of Analgesia and Analgesics is an invaluable practical resource for clinicians giving pain relief in any clinical setting, describing the pharmacologic principles and clinical use of all available pain medications. As well as detailed overviews of pain processing and analgesic theory, sections are dedicated to oral and parenteral opioid analgesics, neuraxial opioids, NSAIDs, local anesthetics, anticonvulsant type analgesics, NMDA antagonists, alpha adrenergic analgesics, antidepressant analgesics, muscle relaxants, adjuvant medications, and new and emerging analgesics. The concise format of the chapters allows for quick and easy reading and assimilation of information. Enhanced by summary tables and figures, each chapter provides an overview of a particular drug, covering chemical structure, mode of activity, indications, contraindications, common doses and uses, advantages and disadvantages, and drug related adverse events. Key references are also provided. Edited by leading experts in pain management, this is essential reading for any clinician involved in pain management"--